1970
DOI: 10.5755/j01.eee.108.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Estimation of Self-Similar Wireless Traffic Relaxation Time and Hurst Coefficient Dependence

Abstract: Analyzed formula can be used for finding system relaxation time depending on what server load is and how high is input traffic self-similarity degree. It was found that the best result is achieved with Verhulst equation. Ill. 6, bibl. 6, tabl. 2 (in English; abstracts in English and Lithuanian).http://dx.doi.org/10.5755/j01.eee.108.2.139

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Authors used (3) in their latest research [4] and showed that system relaxation time serving self-similar traffic can be well approximated by the logistic curve.…”
Section: Logistic Curve and Logistic Ma Pmentioning
confidence: 99%
“…Authors used (3) in their latest research [4] and showed that system relaxation time serving self-similar traffic can be well approximated by the logistic curve.…”
Section: Logistic Curve and Logistic Ma Pmentioning
confidence: 99%